Influência da inclinação de estruturas de cobertura no consumo de madeira - Menezes, Isabella Silva (2022)
Wood is often used in lattice roof structures because of its excellent mechanical properties. Currently, due to the increasingly competitive market and the scarcity of available resources, there has been an increase in demand for structures with a refined design, in which safety is guaranteed with lower consumption of material. A value, commonly recommended by fibercement roof tile manufacturers for lower consumption of wood to be used in the roof structure is the use of a 6° (i=10%) inclination between the truss flanges. In this context, this study seeks to evaluate the influence of the inclination between the flanges of Howe and Pratt-type joists on wood consumption, using iTruss software, which performs structural analysis via FEM and considers the guidelines of the recently published ABNT NBR 7190-1: 2022 standard for design. As this is the main variable of this study, the range of variation for slope considered was from 5º (i=9%) to 25º (i=47%). In order to contemplate the most diverse design situations, two different span sizes will also be considered, in addition to other variable parameters such as wood strength class and moisture class, thus totaling 672 simulations. The 6° slope (i=10%) did not present the lowest consumption for any of the situations analyzed. In order to assist decision-making in structural wood roofing projects, considering the consumption of the entire roof structure (trusses + purlins), an optimal pitch range of 10°(i=18%) to 12°(i=21%) was determined for all situations, so that the consumption obtained within this range does not exceed a 10% increase of the minimum possible consumption for each situation.